2021
DOI: 10.1111/hepr.13608
|View full text |Cite
|
Sign up to set email alerts
|

Mac‐2 binding protein glycan isomer as noninvasive tool to assess liver fibrosis in children with chronic liver disease

Abstract: Aim: This study is aimed to measure the value of serum Mac-2 binding protein glycan isomer (M2BPGI) in children with chronic liver diseases in comparison with liver biopsy and serum biomarkers. Methods: Comparative cross-sectional study included 100 children with chronic liver diseases and 50 healthy age/sex-matched control group. All subjects were evaluated via medical history, clinical, radiological and laboratory examinations. Liver biopsy was performed for studied patients and serum M2BPGI level was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The previous studies on serum biomarkers including APRI, FIB-4, and FibroTest have shown that they are useful for selecting pediatric patients with liver cirrhosis who should undergo a liver biopsy (21)(22)(23)(24). However, chronic hepatitis C generally progresses slowly during childhood with no cases showing liver cirrhosis in our subjects, consistent with reports in previous studies (25,26).…”
Section: Discussionsupporting
confidence: 89%
“…The previous studies on serum biomarkers including APRI, FIB-4, and FibroTest have shown that they are useful for selecting pediatric patients with liver cirrhosis who should undergo a liver biopsy (21)(22)(23)(24). However, chronic hepatitis C generally progresses slowly during childhood with no cases showing liver cirrhosis in our subjects, consistent with reports in previous studies (25,26).…”
Section: Discussionsupporting
confidence: 89%
“…Regarding adults, there are various articles evaluating the diagnostic capability of patients with NAFLD ( 36 39 ). However, regarding children, there are only articles evaluating biliary atresia or multiple diseases together ( 40 43 ). It is of great significance that we evaluated the diagnostic capability of M2BPGi for assessing the advanced fibrosis status in pediatric patients with NAFLD for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on serum biomarkers, including APRI, FIB-4, and FibroTest, have shown that they are useful for selecting pediatric patients with liver cirrhosis who should undergo a liver biopsy 21 24 . However, chronic hepatitis C generally progresses slowly during childhood, with no cases showing liver cirrhosis in our subjects, consistent with reports in previous studies 25 , 26 .…”
Section: Discussionmentioning
confidence: 99%